2015
DOI: 10.1016/j.adolescence.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

The cyclical nature of depressed mood and future risk: Depression, rumination, and deficits in emotional clarity in adolescent girls

Abstract: Deficits in emotional clarity, the understanding and awareness of one’s own emotions and the ability to label them appropriately, are associated with increased depressive symptoms. Surprisingly, few studies have examined factors associated with reduction in emotional clarity for adolescents, such as depressed mood and ruminative response styles. The present study examined rumination as a potential mediator of the relationship between depressive symptoms and changes in emotional clarity, focusing on sex differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 47 publications
5
38
2
2
Order By: Relevance
“…In particular, emotion dysregulation may be one possible mediator of the relationship between emotional abuse and depressive symptoms (Burns, Jackson, & Harding, 2010; Crow et al, 2014; Shields & Cicchetti, 1998); therefore, future research should evaluate and compare multiple affective vulnerabilities to better understand how these stressors confer risk for depression. Further, it is important to note that our measure of emotional clarity had lower levels of test-retest reliability from the Time 1 to Time 3 assessment; however, this is not surprising because adolescence is a turbulent emotional period and emotional clarity continues to change across adolescence (Rubenstein et al, 2015). Additional research should utilize other measures of emotional clarity to replicate these findings, perhaps by including a measure that includes other aspects of emotional intelligence as well.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In particular, emotion dysregulation may be one possible mediator of the relationship between emotional abuse and depressive symptoms (Burns, Jackson, & Harding, 2010; Crow et al, 2014; Shields & Cicchetti, 1998); therefore, future research should evaluate and compare multiple affective vulnerabilities to better understand how these stressors confer risk for depression. Further, it is important to note that our measure of emotional clarity had lower levels of test-retest reliability from the Time 1 to Time 3 assessment; however, this is not surprising because adolescence is a turbulent emotional period and emotional clarity continues to change across adolescence (Rubenstein et al, 2015). Additional research should utilize other measures of emotional clarity to replicate these findings, perhaps by including a measure that includes other aspects of emotional intelligence as well.…”
Section: Discussionmentioning
confidence: 87%
“…This is surprising, as adolescence is a period of continued emotional development, and in which the social environment may be particularly influential in emotional development (Burnett et al, 2011; Casey et al, 2011; Nelson et al, 2005). Further, recent research suggests that emotional clarity may fluctuate throughout the course of adolescence, and youth who develop greater deficits in emotional clarity over time may be at heightened risk for depression (Rubenstein et al, 2015). These findings highlight the importance of examining factors that may hinder the continued development of emotional clarity throughout adolescence.…”
Section: Emotional Clarity As a Mechanism Linking Emotional Neglect Amentioning
confidence: 99%
“…Although some past research indicates that girls tend to rate their emotional intelligence as higher than boys (Ciarrochi, Chan, & Bajgar, 2001), in the context of depression, girls generally experience more risk factors than do boys, such as ruminating in response to depressed mood, engaging in passive coping strategies, and experiencing stressful life events (Hankin et al, 1998; Jose & Brown, 2008; Nolen-Hoeksema, Larson, & Grayson, 1999). Rumination and emotional clarity may be especially linked for girls; Rubenstein and colleagues (2015) found that, for adolescent girls, rumination mediated the link between depression and poor emotional clarity over time.…”
Section: Discussionmentioning
confidence: 93%
“…The literature on emotional clarity is limited, and only a small number of studies have examined its association with depression (Cha & Nock, 2009; Flynn & Rudolph, 2010; Hamilton, Hamlat, Stange, Abramson, & Alloy, 2014; Stange, Alloy, Flynn, & Abramson, 2013; Stange, Boccia et al, 2013; Rubenstein et al, 2015). These studies have generally examined emotional clarity as a moderator in the relationship between stress and other personal vulnerability factors and the occurrence of depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation